2001
DOI: 10.1096/fj.01-0506fje
|View full text |Cite
|
Sign up to set email alerts
|

Intracrine hepatopoietin potentiates AP‐1 activity through JAB1 independent of MAPK pathway

Abstract: Many growth factors and cytokines are involved in liver regeneration. Of them, only hepatopoietin (HPO)/ALR (augmenter of liver regeneration) is a specifically hepatotrophic factor originally identified from the cytosol of regenerating or hyperplastic hepatic cells. Previous reports indicate that extracellular HPO triggers the MAPK pathway by binding its specific receptor on the cell surface. However, its function in the cytosol of hepatocytes is unclear. Here we identified that JAB1 (Jun activation domain-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 30 publications
(50 reference statements)
1
53
1
1
Order By: Relevance
“…Furthermore, we proposed that extracellular HPO stimulates proliferation of hepatocytes and enhances liver regeneration by activating the MAPK signaling pathway under the mediation of HPO receptor (9). Intriguingly, we further found that intracellular HPO can specifically modulate the AP-1 pathway through JAB1 via a MAPK-independent pathway and that HPO enhances the increased phosphorylation level of cJun through JAB1 but has no effect on the expression of transfected c-Jun or endogenous c-Jun N-terminal kinase nor on phosphorylation of c-Jun N-terminal kinase (10).…”
Section: Hepatopoietin (Hpo)mentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, we proposed that extracellular HPO stimulates proliferation of hepatocytes and enhances liver regeneration by activating the MAPK signaling pathway under the mediation of HPO receptor (9). Intriguingly, we further found that intracellular HPO can specifically modulate the AP-1 pathway through JAB1 via a MAPK-independent pathway and that HPO enhances the increased phosphorylation level of cJun through JAB1 but has no effect on the expression of transfected c-Jun or endogenous c-Jun N-terminal kinase nor on phosphorylation of c-Jun N-terminal kinase (10).…”
Section: Hepatopoietin (Hpo)mentioning
confidence: 54%
“…HPO activated AP-1 by increasing c-Jun phosphorylation independent of both c-Jun N-terminal kinase and extracellular signal-regulated kinase 1/2, and the co-localization site of HPO with JAB1 is the nucleus (10). Considering that the CXXC Cys 3 Ser mutants devoid of enzyme activity can also bind to JAB1 and that they can neither increase phospho-c-Jun levels nor activate the AP-1-dependent promoter, our data show that the CXXC motif, the N-terminal amino acid sequences of HPO, and SOX activity are indispensable to its intracellular cytokine effect via JAB1-HPO interaction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it has been elucidated that intracellular ALR may activate transcription factors via a MAPK independent pathway. ALR was shown to bind to JAB1 (c-Jun activating domain-binding protein 1), a coactivator of transcription factor AP-1, and thereby increased AP-1 activity (30,31). Additionally, ALR was found to interact with macrophage migration inhibitory factor (MIF) and inhibit its effect on AP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, human hepatopoietin (HPO), as the Alrp protein is also designated, has been described as a hepatotrophic growth factor that binds to a specific cell surface receptor in hepatocytes and hepatoma cells and induces the stimulation of the mitogenactivated protein kinase cascade (20). In addition to this, intracellular HPO has been shown to interact with the transcriptional coactivator Jun activation domain-binding protein 1, designated JAB1, to regulate AP-1 transcriptional activity (23). Moreover, the potentiation of AP-1 activation by HPO appears to be dependent on its function as a sulfhydryl oxidase (6).…”
mentioning
confidence: 99%